SYMBOL OF LANGUAGE AND NATION (Conferencea, 2023)
In this article, one of the leading linguists of modern Uzbek linguistics, professor Nizomiddn Mahmudov, made a brief comment on the incomparable contribution to the development of Uzbek linguistics and his scientific heritage.